Structural and functional analysis of the putative pH sensor in the Kir1.1 (ROMK) potassium channel. - Rapedius, M; Haider, S; Browne, K; Shang, L; Sansom, M; Baukrowitz, T; Tucker, S (2006)
The pH-sensitive renal potassium channel Kir1.1 is important for K+ homeostasis. Disruption of the pH-sensing mechanism causes type II Bartter syndrome. The pH sensor is thought to be an anomalously titrated lysine residue (K80) that interacts with two arginine residues as part of an 'RKR triad'. We show that a Kir1.1 orthologue from Fugu rubripes lacks this lysine and yet is still highly pH sensitive, indicating that K80 is not the H+ sensor. Instead, K80 functionally interacts with A177 on transmembrane domain 2 at the 'helix-bundle crossing' and controls the ability of pH-dependent conformational changes to induce pore closure. Although not required for pH inhibition, K80 is indispensable for the coupling of pH gating to the extracellular K+ concentration, explaining its conservation in most Kir1.1 orthologues. Furthermore, we demonstrate that instead of interacting with K80, the RKR arginine residues form highly conserved inter- and intra-subunit interactions that are important for Kir channel gating and influence pH sensitivity indirectly.